Zero Base Budgeting Method Applied at Education Expenditures of Cluj-Napoca Budget - Paul ZAI; Adrian Mihai INCEU; Dan Tudor LAZĂR (Transylvanian Review of Administrative Sciences, 2006)
This study is trying to propose alternative methods for budget elaboration, in order to be able to forcast the budget. For presenting the practical part of ZBB (Zero Base Budgeting), we have decided to apply ZBB method for forecasting Cluj-Napoca budget - Chapter Education. To estimate the values of the principal expenditures we will study the data from a budgetary centre, and a tertiary unit. The accuracy of our predictions is trying to underline the necessity of using modern methods for budget elaboration.